Ethical reasoning as contextual predictor of whistle-blowing intention / Saidah Hamizah Ahmad, Mohamad Amirul Ahmad Buniamin and Mohd Farid Mohd Mahali - Ahmad, Saidah Hamizah; Ahmad Buniamin, Mohamad Amirul; Mohd Mahali, Mohd Farid (Faculty of Administrative Science and Policy Studies, 2015)
The move toward better public governance exacerbates the conditions leading to instances of whistle-blowing. The initial prediction of this paper was ethical failure is the ground reason for organizational collapse. This paper provides an analysis of ethical reasoning as an indicator to whistle-blowing intention in Public Sector. The study uses data from questionnaire received from 242 respondents of public agencies in Klang valley for the year 2013. Of greatest importance is the finding that ethical reasoning strongly influences whistle-blowing intention among public servants due to the inherent ethical standing of the individual. Our final analysis calls for the need to refine this research by enumerating the role of culture as a moderating variable in future research.